Influence of high ambient temperature on reproductive performance and physiology of rabbit does in a commercial rabbitry in Greece - XYLOURI-FRAGIADAKI (Ε. ΞΥΛΟΥΡΗ-ΦΡΑΓΚΙΑΔΑΚΗ) E.; GOLIDI (Ε. ΓΟΛΙΔΗ) E.; MENEGATOS (Ι. ΜΕΝΕΓΑΤΟΣ) I.; LUZI, F. (Journal of the Hellenic Veterinary Medical Society, 2018)
The reproductive performance and physiological traits of intensively raised does were evaluated under farm conditions in Greece, during the hot (average farm temperature 19.5°C) and cold period (average farm temperature 12.4°C). The size of litter at birth (6.94 vs. 7.84 alive pups, P<0.001), the size of litter at weaning (5.95 vs. 7.06, P<0.001), the pre-weaning mortality rate (16.94% vs. 9.60%, P<0.001, the number of born dead (0.39 vs. 0.19, P<0.001) and the number of stillborn (0,05 vs 0,02 P<0.01) were significantly affected during the hot period, while litter weight and individual weight at birth did not seem to differ between hot and cold period (461 g vs. 466 g (P<0.05) and 68 vs. 65 g (P<0.05), respectively). Rectal temperature of does and respiration rate were higher in the hot period (39.09°C vs. 38.93°C (NS) and 128.08 respirations/min vs. 115.37 respirations/min; P<0.001). The effects of parity order and animals were also studied revealing that parity order influenced significantly total born, born alive, stillborn and weaned rabbits, litter weight and individual weight at birth, as well as the does’ respiration rate. The interaction between parity and period was not significant for any of the recorded parameters. In conclusion, high ambient temperature impaired does’ reproductive and physiological traits under those conditions, similar to most natural environmental conditions in Greece.